2015
DOI: 10.1093/imrn/rnv103
|View full text |Cite
|
Sign up to set email alerts
|

Dimension Conservation for Self-Similar Sets and Fractal Percolation

Abstract: We introduce a technique that uses projection properties of fractal percolation to establish dimension conservation results for sections of deterministic self-similar sets. For example, let K be a self-similar subset of R 2 with Hausdorff dimension dim H K > 1 such that the rotational components of the underlying similarities generate the full rotation group. Then for all > 0, writing π θ for projection onto the line L θ in direction θ, the Hausdorff dimensions of the sections satisfy dim H (K ∩ π −1 θ x) > di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Another related result for sets is due to Falconer and Jin [FJ2]. They showed that if K ⊂ R 2 is self-similar, with dim K > 1 and a dense rotation group, then for every…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 96%
“…Another related result for sets is due to Falconer and Jin [FJ2]. They showed that if K ⊂ R 2 is self-similar, with dim K > 1 and a dense rotation group, then for every…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 96%
“…Note that the authors of [6] claim dimension conservation almost surely for any fixed direction, but not almost surely for all of them simultaneously. In a following paper [7] the same authors obtain dimension conservation for all directional projections at once in the sense of (3.2). Since the proof is beautiful, we sketch its idea below:…”
Section: Dimension Conservationmentioning
confidence: 85%
“…In the last years several authors received dimension conservation results on projections of fractal percolation sets [6,7,22]. First let us introduce three dimension conservation notions relevant for this paper.…”
Section: Dimension Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…An analogues statement, for self-similar sets with the SSC, was first proven by Furstenberg [Fur]. Another related result for sets is due to Falconer and Jin [FJ2]. They showed that if K ⊂ C is self-similar, with dim K > 1 and a dense rotation group, then for every ǫ > 0 there exists N ǫ ⊂ S, with dim H N ǫ = 0, such that for z ∈ S \ N ǫ the set {x ∈ R : dim H (K ∩ P −1 z {x}) > dim K − 1 − ǫ} has positive length.…”
Section: Introductionmentioning
confidence: 84%